Slash them all - Maillard, Antoine (Fantagraphics Books Inc., 2022)
At the beginning of summer in a small town, two high school students are found dead, and word spreads that a serial killer is on the loose. Panic sends the community into chaos. Meanwhile, evil has plans of its own.